AKSESIBILITAS PEMBERIAN BANTUAN PSIKOLOGIS BAGI PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA OLEH KOMISI NASIONALANTI KEKERASAN TERHADAP PEREMPUAN (CONTOH PUTUSAN NO. 1914/PID.SUS/2020/PN.TNG) - Brigitta Intan Putri (Fakultas Hukum Universitas Tarumanagara, 2022)
In cases of Domestic Violence, victims of domestic violence, most women are entitled to psychologicalassistance for the violence they receive. This has been regulated in Law no. 23 of 2004. However, inpractice there are still women victims of domestic violence who do not receive the psychologicalassistance as stated in Case No. 1914/Pid.Sus/2020/Pn. Tng. In the verdict the victim did not apply forpsychological assistance due to the victim's ignorance. Based on this, the victim needs access topsychological assistance. This accessibility has not been regulated in the legislation. Not all people,especially victims of domestic violence, know how to access psychological assistance.